Dairy imports and import policy in Mali and their implications for the dairy sector in the Bamako area - Massow, V.H. von (International Livestock Centre for Africa, 1985)
Discusses the economic relationship among supply, demand and imports of dairy products in the Bamako area focussing on the influence of government policy on dairy imports. Includes a brief description of production, consumption & trade patterns; the policy measures affecting dairy imports; factors influencing the development of consumption, production & import; and a calculation of economic effects of dairy imports & related policies. Also discusses the role of the dairy plant ULB (Union Laitiere de Bamako) focussing on ULB's price and marketing policy and its economic and financial situation.